Glycovariant Enabled Diagnosis of Renal Cell Carcinoma - Diaz Armas, Claudia (My University, 2019)
Renal Cell Carcinoma (RCC) has the highest mortality rate of the genitourinary cancers. Each year, around 273, 000 new cases are diagnosed. Prognosis for patients diagnosed with RCC is dependent on the stage when it is detected, with about 11% survival rate for advanced types of this cancer. Currently, detection of RCC is mainly incidental while testing for other complications with MRI or computational tomography. Despite their diagnostic accuracies, these techniques have few pitfalls making the need for development of diagnostic assays based on molecular markers more important. In this study, urine and serum from benign kidney disease (n=3) and RCC (n=15) obtained from Ghent, Belgium were used. The aim of the study is to identify RCC-specific glycovariants of glycoproteins like Tamm-Horsfall Protein (THP), Integrin alpha-3 (ITGA-3) and MUC1 (CA15-3. Altered glycosylation patterns are commonly observed in cancers. Such altered glycans can be detected with glycan binding proteins known as lectins. Usually, the binding affinity of lectins to glycans is much weaker compared to antigen-antibody binding. To compensate such weaker binding, we conjugated the lectins to Europium-doped polystyrene nanoparticles. Such nanoparticles increase the binding efficiency through avidity affect. The glycoprofiling of THP, ITGA-3 and MUC1 from pooled samples was performed using a wide variety of lectins with varying binding specificities. The potential candidates which showed differential binding between the pooled samples were then evaluated using individual samples. Although no lectin with RCC-specificity was found, potential candidates for future evaluations were obtained.
Keywords: Renal Cell Carcinoma, Immunoassay, Lectins, Glycoprofile